Types of dietary sugars and carbohydrates, cardiometabolic risk factors, and risk of diabetes: a cohort study from the general Danish population - Marta Trius-Soler; Maja Bramming; Majken K. Jensen; Janne S. Tolstrup; Marta Guasch-Ferré (Nutrition Journal)
Abstract Background The role of carbohydrates in diabetes risk is of particular interest due to conflicting results. This study aims to examine the prospective association between types of dietary carbohydrates (fiber, starch, total sugar, glucose, fructose, lactose, maltose, and added sugar) and the risk of diabetes. Further, this study examines the cross-sectional associations between these nutrients and cardiometabolic risk factors. Methods Danish Health Examination Survey (2007–2008) investigated 76,484 Danes in a representative sample using online questionnaires. Dietary information using a food frequency questionnaire was obtained from 42,836 participants. Information on incident cases of diabetes was obtained from the Danish National Diabetes Register. Cox proportional hazard models were used to estimate Hazard Ratios (95% CI). Multiple linear regression analyses were used to assess the associations between carbohydrate types and cardiometabolic risk factors measured in a subsample of 12,977 participants. Results During a median follow-up of 4.9 years, 970 participants developed diabetes. A higher consumption of fructose, but a lower consumption of glucose was associated with a lower risk of diabetes. In subgroup analyses, these associations were only significant among individuals with other risk factors, such as older age, obesity, low fiber consumption, sedentary behavior, smoking status, and hypertension. Participants with a higher intake of fiber tend to have a lower risk of diabetes and healthier anthropometric parameters compared to those with a lower intake. Conclusions Our findings suggest that a higher intake of dietary fiber and fructose is associated with a lower risk of diabetes and healthier metabolic status, while higher glucose intake is associated with a higher diabetes risk. Graphical Abstract